THE POTENTIAL OF COMBINED ETHANOL EXTRACTS OF SAGA AND SEMBUKAN LEAVES IN REDUCING CHOLESTEROL LEVELS IN HYPERCHOLESTEROLEMIC MICE - Ulfatul Fadila; Gaby Ayu Patricia; Khoirul Ngibad (Universitas Kusuma Husada Surakarta, 2026)
Background: To date, no research has explored the synergistic potential between saga leaves (Adenanthera pavonina L.) and sembukan leaves (Paederia foetida L.) in increasing the effectiveness of lowering cholesterol levels. This study aims to evaluate the potential of the combination of saga leaf ethanol extract and sembukan leaf in lowering cholesterol levels in hypercholesterolemia mice.Methods: The study used 36 mice divided into six treatment groups, including a negative control group, a positive control, a drug control, and a treatment group with different doses of a combination of ethanol extract of Saga leaves and Sembukan leaves. The spectrophotometer measured lipid levels on days 0, 21, and 24. Data analysis was done using the one-way ANOVA test to determine group differences.Results: The analysis showed that the combination of ethanol extract of saga leaves and sembukan leaves significantly reduced the cholesterol levels of hypercholesterolemia mice (p=0.000). The best dose for cholesterol reduction is 56 mg/20 g body weight (BW) with a 66% reduction.Conclusion: Combining ethanol extract of saga leaves and sembukan leaves at a dose of 56 mg/20 g body weight (BW) effectively reduced cholesterol levels in hypercholesterolemia mice. This research may contribute to developing alternative natural therapies to lower cholesterol levels and prevent cardiovascular disease.